Pastoralism and Development Policy in Ethiopia: A Review Study - Abduselam Abdulahi Mohamed (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Pastoralism is a culture, livelihoods system, extensive use of rangelands. It is the key production system practiced in the arid and semi-arid dryland areas. Recent estimates indicate that about 120 million pastoralists and agro-pastoralists life worldwide, of which 41.7% reside only in sub-Saharan Africa (SSA). Pastoralists live in areas often described as marginal, remote, conflict prone, food insecure and associated with high levels of vulnerability. Pastoral communities of Ethiopia occupy 61% of the total land mass and 97% of Ethiopian pastoralists found in low land areas of Afar, Somali, Oromiya, and SNNPR. In spite pastoral areas have significance role in national economy, yet very little consideration was given to pastoral development and policy makers often neglect them, focusing on the interests of agriculture and urban people. The constitution of Ethiopia gives pastoral communities the right to free land grazing, fair use of natural resources, have market access and receive fair price, and not displaced from their own lands. However, pastoralists have faced new problems in recent years, including competition for water and pasture; unrepresented in socio-economic and political activities, ethnic based conflicts, poverty, and uneven drought and climate changes. The government of Ethiopia began large scale efforts to develop the pastoral areas and initiated different projects, but pastoral development policies and strategies seem to be state centrally-driven. In Ethiopia the current nature of pastoralism and pastoral communities’ life style is changing. Therefore, government needs to develop policies and strategies which are based on local customs and practical knowledge.